Immunostimulatory effects of the phenolic compounds from lichens on nitric oxide and hydrogen peroxide production - Carlos, Iracilda Z. [UNESP]; Carli, Camila B. A. [UNESP]; Maia, Danielle C. G. [UNESP]; Benzatti, Fernanda P. [UNESP]; Lopes, Flavia C. M. [UNESP]; Roese, Fernanda M.; Watanabe, Márcio; Micheletti, Ana C.; Santos, Lourdes Campaner dos [UNESP]; Vilegas, Wagner [UNESP]; Honda, Neli K. (Springer Nature, 2009)
The effects of isolated compounds from Brazilian lichens and their derivatives on H 2O 2 and NO production were studied using murine macrophages as a part of an attempt to understand their possible immunomodulatory properties. The compound cytotoxicity was studied using MTT assay. Macrophage stimulation was evaluated by the determination of NO (Griess assay) and H 2O 2 (horseradish peroxidase/phenol red) in supernatants of peritoneal macrophage cultures of Swiss mice. This research demonstrated stimulatory activities of some phenolic compounds isolated from lichens and their derivatives on H 2O 2 and NO production. Structure-activity relationships suggest several synthetic directions for further improvement of immunological activity.
Keywords: Hydrogen peroxide; Lichens; Macrophages; Nitric oxide; Phenolic compounds; 8' o n propyl norstitic acid; 9' o ethyl norstitic acid; 9' o ethyl protocetraric acid; 9' o iso propyl protocetraric acid; 9' o methyl protocetraric acid; 9' o n butyl protocetraric acid; 9' o n hexyl protocetraric acid; 9' o n pentyl protocetraric acid; 9' o n propyl protocetraric acid; 9' o sec butyl protocetraric acid; 9' o terc butyl protocetraric acid; comprotocetraric acid; hydrogen peroxide; immunostimulating agent; lichexanthone; methyl protocetrate; nitric oxide; nitroblue tetrazolium; norstitic acid; phenol derivative; physodic acid; protocetraric acid; unclassified drug; animal cell; cell stimulation; cell viability; cytotoxicity; drug determination; drug structure; drug synthesis; immune response; immunomodulation; lichen; macrophage; mouse; nonhuman; peritoneum; structure activity relation; supernatant; Swiss Webster mouse